Pengaruh lengas tanah terhadap aktivitas nitrat reduktase dan glutamin sintetase beberapa varietas kacang tanah=The influence of soil moisture on nitrate reductase and glutamine synthetase activity in several varietas... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The experiment of the effects of soil moisture on nitrate reductase activity(NRA) and glutamine synthetase(GSA) in several varieties of peanut was conducted in the green house and in the Molecular laboratory_Jember University. The treatments were the combination factors of soil moisture level and peanut variety. The first factor was watering interval to the field capacity (FC), consisted 2 days interval (L1), 4 days interval(L2), 6 days interval(L3), 8 days interval(L4). The second factors was peanut variety consisted of Gajah(V1), Anoa(V2), Macan(V3), and Kelinci variety (V4). The results shown that 1) NRA was influenced more by soil humidity than GSA, 2) GSA had positive corelation with NRA (r=0,667*) at 24 days afterplanting but no correlation had been found from both of them at 47 days after planting, 3) NRA could could be used as selection marker of drought resistance varieties.NRA of Kelinci variety was high at low soil humidity, and implied that Kelinci variety was more resistant to drought.